Metallic CoO/Co heterostructures stabilized in an ultrathin amorphous carbon shell for high-performance electrochemical supercapacitive behaviour. Issue 1 (7th December 2018) - Sun, Xuezhi; Lu, Yongxin; Li, Tongtong; Zhao, Shuaishuai; Gao, Zhida; Song, Yan-Yan
Abstract : A CoO based supercapacitor with high capacity and long-term storage stability is enabled by combining metallic Co-doping and a carbon shell. Abstract : As a highly electrochemically active transition-metal oxide (TMO), cobalt monoxide (CoO) has been extensively investigated for applications in lithium-ion batteries and electrochemical oxygen evolution. However, its capacitive performance has been rarely studied due to the intrinsic low conductivity and poor stability. Here, we report an asymmetric supercapacitor with excellent electrochemical capacity based on an ultrathin carbon shell entrapped Co-doped CoO heterostructure (CoO/Co@C). The metallic conductivity and mesoporous configuration make the as-prepared CoO/Co@C deliver a dramatic specific capacitance of 2165.7 F g −1 at a scan rate of 10 mV s −1 . Besides the contribution to double-layer capacitance, more importantly, the amorphous carbon shell effectively prevents the CoO/Co heterostructure from further oxidation, thus resulting in a significantly improved long-term storage stability in air. An asymmetric supercapacitor cell fabricated using CoO/Co@C and active carbon achieves a maximum energy density of 146.3 W h kg −1 at a power density of 1800 W kg −1, and the maximum of 27 000 W kg −1 can be obtained with a remaining energy density of 63.0 W h kg −1 . The easy preparation, high performance, and excellent cycling stability of the CoO/Co@C nanocomposite make it a promising material for catalyst and battery applications.